The Implementation of Classroom Management Principles in Teaching English at Vocational High School 3 Padang - Suparmi (Universitas Putra Indonesia YPTK Padang, 2021)
The aim of this research was to find out how the teachers implemented principles of classroom management in teaching and learning process at SMKN 3 Padang during teaching and learning process. This is a qualitative research. The data were the result of observation and interview. The participants of this research were three English teachers of SMKN 3 Padang who teach at grade X, XI and XII. The finding of this research indicates that English teachers at SMKN 3 Padang do not implement almost all of the principles of classroom managements during teaching and learning process. They implemented them in three stages of teaching; such as pre-activity, whilst-activity and post activity. Almost all of the principles of classroom management are implemented in whilst-activity. At pre and post-activity, the teacher only implemented three principles, such as warm and enthusiasm, emphasizing on the positive things and building self-discipline. Moreover, the data shows the teachers’ reasons in implementing classroom management. The reason is increasing students’ motivation and achievement. It can be concluded that the English teachers at SMKN 3 Padang should improve their focuses to the principles of classroom management in teaching English. Hopeful, this research can be a significant contribution for English teachers in teaching.